Evaluating transgender youth and parent interest and preferences regarding support groups - Shauna Marie Lawlis MD; Patrick Butler PhD, LCSW; Amy Middleman MD, MSEd, MPH (SAGE Publishing, 2020)
The purpose of this cross-sectional survey study is to explore transgender teens' and their parents' interest in and preferences regarding support groups in an effort to optimally serve the entire family's needs. The aims of the study were to: (1) describe transgender teens interest level and preferences regarding support groups; (2) describe parents of transgender teens interest level and preferences regarding support groups; and (3) compare responses based on demographics including teens versus parent, natal sex, and gender identity. De-identified surveys were collected from a convenience sample of transgender patients (N = 26), ages 13-18 years, and their parents (N = 20). Overall level of interest in support groups was 7.20/10 for youth and 7.95/10 for parents where 0 is not interested and 10 is very interested. Both groups endorsed benefits of a support group, including help with managing school issues, learning about local resources for transgender teens, and providing peer support. Both groups indicated "no time" as the most common potential barrier to attendance. Both groups expressed moderate interest in support groups, with minor differences between youths and parents noted in preferred support group structure. Further examination is warranted to determine optimal support group characteristics aimed specifically at parents and, separately, for youth. Additional support services might complement groups for a more comprehensive approach to support resources for this community.